POWER, REVOLUTION, AND BUSINESS IN POST-REVOLUTIONARY GEORGIA (Part One) - DOLIDZE, Valerian (CENTRAL ASIA AND THE CAUCASUS, 2006)
There is the opinion that the method by which a political leader is replaced, or his own attitude to his possible loss of power, is part of his political heritage and affects the country’s democratic development. If the first leader of a newly formed political system is replaced, this heritage becomes even more important.1 The point is amply illustrated by fifteen years of Georgia’s political independence. It changed its political leaders twice, each time with violence and vi-olations of the Constitution. Each time the change was carried out under democratic banners, and each time authoritarian trends in the country’s political system became more pronounced: after coming to power each of the new leaders wanted to preserve it. To achieve this, they sought for eco-nomic domination to get a grip on badly needed material and financial resources. So each of the new leaders tried to place private business under his political control. The Georgian Constitution, however, guarantees protection of private property; the new leaders are also limited by the liber-al Constitution in many other respects, the country’s financial and political dependence on the West, and its desire to integrate into the Europe-an structures. This forces each of the new leaders to use methods which will not damage the country’s democratic image. Political pressure on the business community became especially obvious after the Rose Revolution; today it is barely concealed and rather harsh.